Pembaharuan Hukum Keluarga Islam Tentang Hak Pengasuhan Anak (Hadlanah) Akibat Perceraian dalam Kompilasi Hukum Islam (Khi) dan Undang-Undang Nomor 35 Tahun 2014 tentang Perlindungan Anak - Najib, Afifun Najib (Cv. Kalimasada Group, 2025)
Child custody (hadlanah) is a common problem in today's society. The act of divorce between husband and wife can have implications for child custody rights. Divorced parents leave behind a secondary problem, namely to whom the child custody rights are given after the divorce occurs. It is possible that the child is cared for by one of the parents, perhaps by the wife and/or her family or also by the husband and/or his family. Other reasons for the existence of child custody matters can be because the child does not have parents, the child who was indeed given by his biological parents to foster parents for example for economic reasons, or because the husband and wife who do not yet have children are caring for someone else's child. The effort to care for children is the obligation of the family from the child as a guarantee of his future. This is the academic problem that this study wants to explain. The important issue studied in this research is how the renewal of Indonesian Islamic Family Law in child custody rights and how the authority of child custody is in Indonesian Islamic Family Law. The purpose of this dissertation research is to study in depth the renewal of Indonesian Islamic Family Law in child custody rights and to conduct an analysis of the authority of child custody in Indonesian Islamic Family Law. This type of research is normative legal research with library research, while the research method used is a statute approach and a conceptual approach. There are two data sources used, namely primary data sources (main) and secondary data sources (supporting). Data collection and processing through the stages of editing, coding, reconstructing and systematizing. Data analysis through content analysis shows an integrative analysis method and conceptually tends to be directed at finding, identifying, processing and analyzing data to understand its meaning, significance and relevance. From the results of the study, it can be concluded that there are several Indonesian laws and regulations that regulate child custody rights (hadlanah) as a legal umbrella for foster parents to guarantee the future of the child. According to Islamic law, children and their parents cannot be separated because both are bound by lineage. Likewise, child care by parties other than their biological parents who are involved in a divorce does not affect the child's relationship by lineage with their biological parents. Therefore, the implementation of child custody rights must go through a legal process to avoid things that are detrimental (madharat). Therefore, the determination of child custody rights must be based on applicable laws and regulations. The positive value of implementing a formal legal process as a binding for foster parents is that there are obligations that must be fulfilled and there is legal certainty. Existing laws and regulations can be supported by Government Regulations on the protection of child custody rights.